Milk production economics and micro financing impacts in Chhotanagpur platue of Jharkhand - Sinha, Mukesh Kumar; Dhaka, J P; Meena, M S (The Indian Journal of Animal Sciences, 2012)
The study examined impacts of micro credit on milk production and factor productivity among tribal farmers of Chhotanagpur platue. Sample responses of 240 farmers were analysed for this study. The impact was evaluated with the benefits accrued by the beneficiaries over non-beneficiaries with respect to economic parameter of investment pattern, cost of production and income component from dairying. The study revealed that investment made on beneficiary households (Rs 14398.88) was almost double than non-beneficiary households (Rs 7506.20). The gross income from dairy enterprise on beneficiary (Rs 14372) was higher than that of non-beneficiary (Rs 10032.72). The difference in net income, and family labour income was even more pronounced than that of gross income. Marginal value productivity of operational expenses was positive (2.01) and significant, needs priority. The study observed a very positive and favourable response of micro credit to the tribal dairy farmers, needs a continued support for improved income, nutrition and sustained livelihood.